Современное оборудование для сварки трением - Зяхор, И.В. (Автоматическая сварка, 2001)
Проанализированы современные тенденции развития оборудования для сварки трением, а также особенности конструирования машин для различных ее модификаций - конвенционной, инерционной и комбинированной. Описаны работы, проводимые в ИЭС им. Е. О. Патона с целью создания оборудования для сварки трением. Предварительно краткое описание особенностей конструкции установки СТ-120, которая может стать базовой моделью дл нового поколения машин. Current trends in development of equipment for friction welding and peculiarities of design of machines for its modifications, such as conventional, inertia and combined friction welding, are analysed. The work performed at the E.O. Paton Electric Welding Institute in the area of development and manufacture of the friction welding facilities is described. Peculiarities of design of the ST-120 machine, which can serve as the baseline model for a new generation of the friction welding machines, are presented.